1989
DOI: 10.1515/zna-1989-0208
|View full text |Cite
|
Sign up to set email alerts
|

Extended Analysis of the Rotational Spectrum of HCCF

Abstract: The microwave spectrum of fluoroacetylene (HCCF) has been measured in the frequency region 35 -260 GHz. Rotational constants of the ground state and rotational as well as rotation-vibrational interaction constants of several excited states of the C - C - H (ν4) and the C - C - F (ν5) bending vibrations have been obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
9
2
Order By: Relevance
“…Our reinvestigation revealed that the value of H 0 cannot be determined from our experimental data (neither from those obtained in our former investigation (19) nor from those of the present one), since its contribution to the measured frequencies is in the order of the measurement errors. This is a result of its smallness (the value of H 0 obtained by Dore et al (27) is only 0.00020(3) Hz), its J -dependence, and the range of our data.…”
Section: Iv1 the Vibrational Ground State (000)contrasting
confidence: 75%
See 4 more Smart Citations
“…Our reinvestigation revealed that the value of H 0 cannot be determined from our experimental data (neither from those obtained in our former investigation (19) nor from those of the present one), since its contribution to the measured frequencies is in the order of the measurement errors. This is a result of its smallness (the value of H 0 obtained by Dore et al (27) is only 0.00020(3) Hz), its J -dependence, and the range of our data.…”
Section: Iv1 the Vibrational Ground State (000)contrasting
confidence: 75%
“…A most recent MMW-and subMMW-study on the rotational spectrum of the vibrational ground state carried out by Dore et al (27) revealed a noticeable discrepancy between the newly determined value of the 6th order centrifugal distortion constant H 0 and the value previously published by us (19).…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations